PENGARUH PENGGUNAAN KB SUNTIK TERHADAP PENINGKATAN BERAT BADAN DI WILAYAH KERJA PUSKESMAS BUMIWONOREJO KABUPATEN NABIRE PROVINSI PAPUA TENGAH - Mahmud, Siti Hawa; Rahmawati; Syafar, Muhammad (Bina Generasi : Jurnal Kesehatan, 2025)
Background The National Family Planning Movement is primarily focused on controlling the population growth rate and planning human resources. Preventing successive pregnancies is one of the objectives of using contraceptives. Injectable contraception is a practical and effective method of contraception. It is one of the most widely used contraceptive methods in Indonesia. However, one of the side effects of injectable contraception is the potential increase in body weight. Objective The purpose of this research is to determine the impact of injectable contraceptive use on weight change in the working area of the Bumiwonorejo Public Health Center, Nabire Regency, Central Papua Province in 2024. Method (The research method employed is quantitative, aiming to collect numerical data that can be statistically analyzed. This study uses a cross-sectional research design. The collected data are analyzed using the Chi-square test. The Chi-square test is a statistical test used to examine the relationship between two nominal variables. Result From the results we obtained, it appears that out of the seven variables we studied, not all of them have significant values. The variables that show significance are age and physical activity. Therefore, it can be concluded that age is the most influential variable. Conclusion There are two variables that have a significant influence, namely the age variable and the physical activity variable. Meanwhile, the variables of type of contraception, duration of contraceptive use, level of knowledge, parity, and diet of the acceptor, did not indicate a significant influence.